Experimental Study of Copper Alloys by Electronic Speckle Pattern Interferometry - Bakošová, Dana (Manufacturing Technology Journal, 2019)
Electronic Speckle Pattern interferometry (ESPI) is a non-destructive optical method for studying surface deformations. It relies on the interference between diffusely reflected light from the test object and a reference beam. This is one of the most sensitive interferometric technique, so that we can measure sub-micron level displacements either in plane or out of plane. In this study, experimental investigation of vibration behaviour of square copper alloys plates by electronic speckle pattern interferometry is employed. Resonant frequencies and corresponding mode shape are obtained experimentally using the introduced method. Frequencies of resonant vibrational modes depend on elastic properties of material, especially on Young's modulus E, Poisson ratio μ and density of material ρ. This fact gives us in principle the possibility to estimate th e elastic constant of materials from the vibrational measurement. The numerical calculations by the finite element method are performed and the results are compared to the experimental measurements.
Keywords: Electronic Speckle Pattern interferometry; Copp er alloys; Young's modulus; Poisson ratio; Finite element method